Strategi Kepala Madrasah Dalam Peningkatan Kompetensi Pedagogik Guru - Lya Damayanti; Rahmat Rahmat (THE JOER: Journal Of Education Research, 2022)
The problems faced in the world of education are unprofessional educational resources, incompetence educators, low budget, incomplete facilities and infrastructure, poor education management which are considered as weak recources in realizing the goals to be achieved. Every effort to increase the pedagogic competence of teachers at MA Hasanuddin Jombang can give good results, followed by the competence and motivation of teachers to improve and develop their abilities. So the strategy of Islamic School Principle in improving the pedagogic competence of teachers is very important in the world of education. This study aims to 1) determine the pedagogical competence of teachers at MA Hasanuddin Jombang, 2) Analyze the strategies of the head of madrasah in increasing the pedagogical competence of teachers at MA Hasanuddin Jombang and 3) Analyze the inhibiting factors of the principal's strategy in increasing the pedagogical competence of teachers at MA Hasanuddin Jombang. The type of research used in this research is qualitative research with a case study approach and data collection techniques used are observation, interviews and documentation. The results showed that the pedagogic competence at MA Hasanuddin Jombang was good if it met the indicators, namely: 1) Mastery of learning theory and 2) Curriculum development. The strategy of the head of madrasa in improving the pedagogic competence of teachers at MA Hasanuddin Jombang, they are: 1) Empowering educators and staff, 2) Completion of tasks, 3) Application of leadership principles, 4) Good cooperation. The factors that hinder the Islamic School principal's strategy in increasing teacher pedagogic competence at MA Hasanuddin Jombang are: 1) Ability Factors and 2) Motivation Factors.